2018
DOI: 10.1371/journal.pone.0202972
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child attachment in children born preterm and at term: A multigroup analysis

Abstract: ObjectiveWhile ample research exists about mother-child attachment, so far little focus has been on specifics of father-child attachment. Even less research is available on the nature of the father-child relationship for children born preterm. The objective of this study was to determine whether children born preterm (23 to 37 weeks gestation) differ in their attachment to their fathers and mothers from their term peers (> 37 weeks gestation), and whether specific child characteristics, such as gender, twin st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 51 publications
0
19
0
2
Order By: Relevance
“…These results might have important implications for parent-child attachment as recent research has indicated that child-focused RF but not self-focused RF of parents is related to children's attachment security (Borelli, St. John, Cho, & Suchman, 2016). Because mentalization is an essential step to build up and maintain an attachment with children, not surprisingly, father-child attachment scored lower in preterm than at-term children (Ruiz, Piskernik, Witting, Fuiko, & Ahnert, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…These results might have important implications for parent-child attachment as recent research has indicated that child-focused RF but not self-focused RF of parents is related to children's attachment security (Borelli, St. John, Cho, & Suchman, 2016). Because mentalization is an essential step to build up and maintain an attachment with children, not surprisingly, father-child attachment scored lower in preterm than at-term children (Ruiz, Piskernik, Witting, Fuiko, & Ahnert, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…2 In the literature, similar results were found in national and international studies on the theme of support, highlighting its importance during the processes. 2,4,19,20 Caring requires the establishment of a face-to-face relationship, which Schütz defines as one in which the subjects involved are aware of each other and are facing each other in the same time and space. 16 Fathers need to be protagonists of their children's care in a NICU, however, they are still seen as supporting actors, especially after the arrival of the mother in this scenario, having their access restricted to visiting hours.…”
Section: Discussionmentioning
confidence: 99%
“…However, this same environment, capable of keeping their baby alive, is responsible for the interruption of the first contacts between father and child. 4,20 Another important fact is related to the current family configuration, in which the emergence of a more affective father model is observed, as well as a more participative model in activities related to the family, which contradicts the hegemonic paternity model. 1,2 The activity of recording the photographic images of the preterm child during hospitalization provided motivation, that is, a stimulus during the understanding of the care process.…”
Section: Discussionmentioning
confidence: 99%
“…While in the neonatal intensive care unit (NICU), the preterm infant's brain requires nurturing, that being responsive and sensitive caregiving, in order to develop optimally [1]. Maternal sensitivity is the primary predictor of long-term mother-infant attachment [2] and less secure attachment has been found in 1 to 3 years of age children born preterm compared to children born at term [3]. An increase in maternal sensitivity also predicts larger gray matter volume and head circumference in a general population of infants [4].…”
Section: Background and Rationalementioning
confidence: 99%